Pengaruh Latihan Power Tungkai Terhadap Kemampuan Tendangan Lurus Pada Atlet Pencak Silat Perguruan Setia Hati Terate Ahuru Ambon - Dolhamau, Musa; Latar, Idris Moh; Rumahlewang, Emma (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2022)
The purpose of this study was to determine whether there was an effect of leg muscle power training on the ability of straight kicks in Pencak Silat athletes from Setia Hati Terate Ahuru Ambon School. The research design used one group pre-test-post test. There are 2 (two) variables in this study, namely the independent variable (X) leg muscle power with indicators one step-jump, two leg-jump, vanch-jump, and kich-jump, dependent variable (Y) straight kick ability with indicators is the number of kicks. The population used in this study were male and female silat athletes from the Setia Hati Teratai school, totaling 15 people from green to white belt holders. Considering that the population has 7 green belts and 8 white belts, this study is a population study. The results of the study explained that leg muscle power training had a significant effect on the ability to kick straight. These results explain that there is an increase in the ability of straight kicks in the pencak silat athlete Setia Hati Teratai, Ahuru Ambon.Abstract is a summary that explains the entire contents of the article. The abstract contains objectives, methods, results and conclusions. Minimum number of 150 and a maximum of 200 words. Abstract written in Indonesian and English